User guide to experimental auctions of vegetatively propagated seed. RTB User Guide - Delaquis, Erik; Kilwinger, Fleur B.M.; Slavchevska, Vanya; Rajendran, S.; Kikulwe, Enoch Mutebi; Newby, Jonathan Craig (International Potato Center, 2021)
Experimental auctions are used to understand the value of different products to consumers through estimations of willingness to pay (WTP). This information is valuable for many reasons, from obtaining local prices attached to seed traits to informing seed businesses about acceptable production costs. Experimental auctions do a better job of estimating this than simple questionnaires or surveys. By engaging participants actively, experimental auctions lead to real or hypothetical consequences that make people think and act carefully according to their personal preferences. This user guide provides an overview of different types of experimental auctions and their use in seed system research. The guide discusses the structure of auctions, planning and conducting them, and lessons from the field. Reading this guide will help you to be prepared to design and implement an auction in your own project or intervention.